Soluble Urokinase-Type Plasminogen Activator Receptor Levels in Patients With Schizophrenia - Nielsen, Jimmi (Schizophr Bull, 2015)
Background: The etiology of schizophrenia remains largely unknown but alterations in the immune system may be involved. In addition to the psychiatric symptoms, schizophrenia is also associated with up to 20 years reduction in life span. Soluble urokinase-type plasminogen activator receptor (suPAR) is a protein that can be measured in blood samples and reflects the levels of inflammatory activity. It has been associated with mortality and the development of type 2 diabetes and cardiovascular disease. Methods: suPAR levels in patients with schizophrenia were compared to healthy controls from the Danish Blood Donor Study. SuPAR levels were dichotomized at >4.0 ng/ml, which is considered the threshold for low grade inflammation. A multiple logistic regression model was used and adjusted for age, sex, and current smoking. Results: In total we included 1009 subjects, 105 cases with schizophrenia (10.4%) and 904 controls (89.6%). The mean suPAR values were 4.01 ng/ml (SD = 1.43) for the cases vs 1.91 ng/ml (SD = 1.35) for the controls (P < .001). Multiple logistic regression with odds ratio (OR) for suPAR levels >4.0 ng/ml yielded: schizophrenia, OR: 46.15 95% CI 22.69–93.87, P < .001; age, OR: 1.02 95% CI 0.99–1.02, P = .15; male sex, OR: 0.70 95% CI 0.35–1.36, P = .29; and current smoking, OR: 3.51 95% CI 1.78–6.94, P < .001. Conclusions: Patients with schizophrenia had significantly higher suPAR levels than healthy controls. Further studies are warranted to clarify if elevated suPAR levels are involved in the pathophysiology of schizophrenia and/or the increased mortality found in patients with schizophrenia.